Oestrogen conjugates of human late-pregnancy urine - Smith, E. R. (1967)
1. The separation of the oestrogen conjugates in late-pregnancy urine into two groups, peaks I and II, by gel filtration on Sephadex G-25 (Beling, 1963) has been shown to be affected by the presence of urate, which delays the elution of peak II conjugates. 2. By reapplication to a Sephadex column, peak I conjugates have been further separated into two groups (peaks IA and IB) and the metabolites in urine effecting this separation have been studied. 3. Further analysis of the mixed conjugates in the main groups IA, IB and II by ion-exchange and partition chromatography has led to the identification of some of the conjugates present. 4. Oestriol 3-sulphate 16α-glucuronide and 16α-hydroxyoestrone 3-sulphate 16α-glucuronide have been identified in peak IA. 5. The main components of peak IB have been identified as oestrone 3-glucuronide and oestriol 3-glucuronide. 6. The major conjugate in peak II was oestriol 16α-glucuronide and no oestriol 17β-glucuronide was found; small amounts of the ring-d monoglucuronides oestradiol 17β-glucuronide, 16-epioestriol 16β-glucuronide and 16α-hydroxyoestrone 16α-glucuronide were found in this fraction. 7. The behaviour of synthetic oestrogen monoglucuronides has been used as a guide in separation.